The lexical and vocabulary development in the english teaching – learning process with students of eighth year of general basic education at “san josé de guaytacama” educative unit, during the academic cycle april - august 2015 - Unaucho Sánchez, Laura Elizabeth (2015)
This present investigate work was focused on fortifying the communicative area through the use of lexical and vocabulary in the English Teaching-Learning Process in order that students can understand and develop the communicative skills. The main problem was that students were not developing their vocabulary and it makes that they cannot speak in English. Even though that teachers have focused on teaching English language, there has been a little inconvenience at moment to teach and develop the students’ lexical and vocabulary. That is the reason why, it has been designed a Mini Dictionary and some activities to develop them. This investigation was focused on design a Mini Dictionary based on Lexical….